2001
DOI: 10.1128/mcb.21.12.4005-4015.2001
|View full text |Cite
|
Sign up to set email alerts
|

Impaired DNA Damage Response in Cells Expressing an Exon 11-Deleted Murine Brca1 Variant That Localizes to Nuclear Foci

Abstract: Both human and mouse cells express an alternatively spliced variant of BRCA1, BRCA1-⌬11, which lacks exon 11 in its entirety, including putative nuclear localization signals. Consistent with this, BRCA1-⌬11 has been reported to reside in the cytoplasm, a localization that would ostensibly preclude it from playing a role in the nuclear processes in which its full-length counterpart has been implicated. Nevertheless, the finding that murine embryos bearing homozygous deletions of exon 11 survive longer than embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 59 publications
10
96
0
2
Order By: Relevance
“…Consistent with these findings, mouse embryonic fibroblasts (MEFs) carrying a targeted homozygous deletion of exon 11 (which contains ffi 60% of the Brca1 coding sequence) exhibited a defective G2/M checkpoint and extensive chromosomal anomalies (Huber et al, 2001). These Brca1-defective MEFs showed centrosome amplification with multiple functional centrosomes, which led to unequal chromosome segregation and aneuploidy (Xu et al, 1999b).…”
Section: Functional Activities Of Brca1 Cell Cycle Regulation and Gromentioning
confidence: 70%
See 3 more Smart Citations
“…Consistent with these findings, mouse embryonic fibroblasts (MEFs) carrying a targeted homozygous deletion of exon 11 (which contains ffi 60% of the Brca1 coding sequence) exhibited a defective G2/M checkpoint and extensive chromosomal anomalies (Huber et al, 2001). These Brca1-defective MEFs showed centrosome amplification with multiple functional centrosomes, which led to unequal chromosome segregation and aneuploidy (Xu et al, 1999b).…”
Section: Functional Activities Of Brca1 Cell Cycle Regulation and Gromentioning
confidence: 70%
“…Fan et al (2001b) found that a truncated BRCA1 protein containing only the N-terminus (aa 1-302) enters the nucleus. Similarly, a BRCA1 mutant protein corresponding to a naturally occuring isoform (Brca1 D exon 11) enters the nucleus despite the fact that this isoform is missing both NLS1 and NLS2 (Huber et al, 2001). These findings suggest the presence of a cryptic (i.e., non-classical) NLS within the first 300 or so aa of BRCA1.…”
Section: Brca1 Proteinmentioning
confidence: 97%
See 2 more Smart Citations
“…The Brca1 2D11 mutation has an in-frame deletion of exon 11 that results in production of a hypomorphic protein resulting from in-frame splicing from exon 10 to exon 12. This BRCA1 D11 variant has an intact RING domain, tandem BRCT-repeats and localizes to the nucleus, but is associated with a defect in HR-mediated repair (Huber et al, 2001). Unlike homozygous null-BRCA1 mutants, which show early embryonic lethality that is only modestly delayed by being placed in a p53 2/2 background, homozygous Brca1 D11/D11 mutants show mid-gestational embryonic lethality that can be reversed in certain strain backgrounds or by breeding to a p53 +/2 genotype (Cressman et al, 1999a;Xu et al, 2001).…”
Section: Bp1 and Brca1: Synthetic Viabilitymentioning
confidence: 99%